The Impact of Changes in International Dynamics on Defense Policy - Aris Sarjito (LPPM STIA Lancang Kuning Dumai, 2023)
The purpose of this research is to explore the path of change in international dynamics toward defense policy. With the world becoming increasingly connected, the role of defense policy in ensuring the safety and security of nations is becoming increasingly important. This study aims to analyze how international dynamics have changed the defense policies of various countries over the years. The research follows a qualitative design methodology, in which data from various sources including academic literature, policy documents, and expert interviews are collected and analyzed to understand the impact of changing international dynamics on defense policy. Analyzes were conducted at both the individual and collective levels, including specific case studies and broader comparative analyses. The findings of this study indicate that changes in international dynamics have a significant impact on defense policy. The emergence of new global powers and non-state actors, changes in economic and political alliances, and advances in technology are some of the main factors influencing the direction of defense policy over the years. Research reveals that countries are increasingly focusing on developing technologically advanced weapons and defense systems to counter emerging threats such as cyber-attacks and terrorism. In addition, research shows that military alliances and partnerships are becoming increasingly important in shaping defense policy. Countries engage in multilateral cooperation to pool resources and expertise to address common challenges, which in turn leads to the development of common defense policies and strategies. Keywords: defense policy, defense strategy, international dynamics